RTHP-02. IMPACT OF 18F-DOPA PET ON RADIOTHERAPY TARGET VOLUMES FOR NEWLY DIAGNOSED MGMT UNMETHYLATED GLIOBLASTOMA PATIENTS; PRELIMINARY RESULTS OF A PHASE II DOSE-ESCALATION TRIAL. (5th November 2018) - Brinkmann, Debra; Pafundi, Deanna; Hunt, Christopher; Lowe, Val; Yan, Elizabeth; D Brown, Paul; Zakhary, Mark; Zhang, Yan; Seaberg, Maasa; seum Wan Chan Tseung, Hok; Sarkaria, Jann; Laack, Nadia
Abstract: BACKGROUND: Multiple studies have demonstrated that amino acid PET tracers identify aggressive disease beyond what is contrast enhancing on T1-weighted conventional MR (T1CE). In this study, we explored discrepancies between 18F-DOPA PET and conventional MR for defining target volumes in newly diagnosed glioblastoma (GBM) radiotherapy patients. METHODS: In an ongoing NCI-funded trial (NCT:R01CA178200), 18F-DOPA PET was acquired prior to chemoradiation for newly diagnosed GBM patients and incorporated prospectively into the target volumes, modifying low and high dose target volumes, and guiding dose escalation to the most aggressive disease. Based on the results of our pilot biopsy-validation study, two 18F-DOPA PET volumes were defined, one with a T/N threshold >2.0 (PET_high) depicting the most aggressive disease and another with a T/N threshold default of ≥1.5 (PET_low) with modifications if needed by a Nuclear Medicine physician. Both PET volumes were compared with the T1CE+cavity MR volumes for 30 MGMT unmethylated newly diagnosed GBM patients. RESULTS: The PET_low volume extended beyond T2-FLAIR signal abnormality for all patients, and extended beyond standard CTV expansion in 60% of patients. Sixty-seven per cent of patients had at least 20% of the PET_high uptake outside the T1CE volume, and would not have been covered by standard CTV expansion in 8% of patients. The average (range) Dice Similarity Coefficient comparing T1CE with PET_high was 0.3(0.0–0.7). The average (range) Haursdorff maximum distance (cm) between PET uptake and T1CE was found to be 2.4(0.9–7.1). CONCLUSIONS: 18F-DOPA-PET identified regions of biologically active disease outside the T1CE in 67% of patients with significant discordance in volumes. Evaluation of the impact prospective 18F-DOPA PET guidance for dose escalated radiation therapy is under investigation in the ongoing trial.